Effect of acupuncture on episodic memory for amnestic mild cognitive impairment based on hippocampal subregion: study protocol of a randomized, controlled trial - Li, Xinbei; Lu, Xingying; Ou, Juan; Lyu, Hanqing; Liu, Yongfeng; Zhang, Jinhuan (Frontiers in Neurology, 2025)
BackgroundThe hippocampus is a key brain region for episodic memory, and impairment of episodic memory is the earliest feature of amnestic mild cognitive impairment (aMCI). Preserving the structure and function of the hippocampus plays a key role in preventing progression to Alzheimer’s disease (AD). Therefore, early intervention is crucial, and acupuncture could significantly improve episodic memory in aMCI, but the mechanism is not clear. Accordingly, this experiment aims to explore the mechanism of acupuncture to improve episodic memory in aMCI based on the hippocampal subregion.MethodsA randomized, controlled, blinded research will be performed. 150 aMCI participants will be assigned to the verum acupuncture group, sham acupuncture group, and waiting group; 50 healthy controls will also be recruited. Patients in the acupuncture group will receive real acupuncture treatment or placebo acupuncture three times per week, 36 sessions over 12 consecutive weeks in total. Patients in the waiting group will receive the same verum acupuncture treatment for compensation after the trials are finished. The primary outcome will be the auditory-verbal learning test. Secondary outcomes will include Montreal Cognitive Assessment (MoCA), Mini-Mental State Examination (MMSE), Hamilton Depression Scale (HAMD), and functional magnetic resonance imaging data. Outcomes will be measured at baseline and 12 weeks after randomization. Repeated measurement analysis of variance will be used to explore the intervention effect.DiscussionThis protocol will provide theoretical support for the neural mechanisms by which acupuncture improves episodic memory in aMCI. We hope that this study will provide objective evidence and offer alternative treatment options for the early treatment of aMCI.Clinical trial registrationChiCTR2400084308.